Pengaruh Pendapatan, Kepercayaan, Dan Pengetahuan Terhadap Minat Membayar Zakat (Studi Pada Karyawan Di Kawasan Mega Kuningan) - Abdul Majid, Rayhan; Sardiana, Anna (At-Tamwil: Journal of Islamic Economics and Finance, 2023)
This article aims to explain the influence of income, Religiosity, and knowledge of private employees on interest in paying zakat at Amil Zakat Institutions and Zakat Management Organizations (LAZ/OPZ). Data was collected using questionnaires distributed to private employees in the Mega Kuningan area, South Jakarta with a sample of 100 people. This type of research is quantitative descriptive research with a purposive sampling method. This research was analyzed using multiple regression analysis through the IBM SPSS Statistics 22 program. From the results of the t test (partially) the independent variables income (X1), trust (X2), and knowledge (X3) each have an influence on the dependent variable Interest in Paying Zakat (Y). And from the results of the F test, all of these independent variables also simultaneously influence the dependent variable of interest in paying zakat.